Evaluating the Role of Advanced Energy-Efficient Technologies in Promoting Sustainability in Nigeria's Construction Industry - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma (Jurnal Pengabdian KOLABORATIF, 2026)
This study evaluates the impact of advanced energy-efficient technologies on sustainability within the Nigerian construction sector, focusing on their effects on energy consumption, cost reduction, environmental benefits, and social impacts. A quantitative research approach was employed, using structured questionnaires administered to a total of 123 construction professionals across 150 infrastructure projects in Nigeria. The respondents included architects (n=30), civil and structural engineers (n=38), project managers (n=32), and other construction specialists such as quantity surveyors and support staff (n=23). The analysis included descriptive statistics, ANOVA, and multiple regression analysis to evaluate the relationships between technology adoption and sustainability outcomes. The results indicate strong consensus among respondents that energy-efficient technologies lead to reduced energy consumption (mean=4.2, SD=0.83) and long-term cost savings (mean=4.0, SD=0.92). Environmental benefits were rated highly (mean=4.3, SD=0.68), while social impacts were perceived as less significant (mean=3.7, SD=0.75). ANOVA results revealed statistically significant differences in perceptions based on professional roles (F(3,119)=5.24, p=0.002), with architects showing the strongest agreement regarding the effectiveness of these technologies. Multiple regression analysis identified perceived cost savings (β=0.34, p
Keywords: Cost Reduction; Environmental Impact; Nigerian Construction Sector; Social Benefits; Sustainability